Strengthening Egypt's Cereal Sector: Policies for Food Security and Sustainable Development - Dhehibi, Boubaker; Salem, Shaban Ali; Abda-Allah Abdallah, Iman; Souissi, Asma; Baum, Michael (2025)
Cereals are fundamental to Egypt's diet and economy, serving as dietary staples, key agricultural products, and essential trade commodities. Wheat and rice, particularly wheat, are vital to Egyptian diets, with subsidized baladi bread being a cornerstone of food security for most of the population. Cereals contribute significantly to daily caloric intake, providing an affordable food source crucial for social stability. They occupy nearly 46% of Egypt’s cropped area, including wheat, maize, sorghum, barley and rice, while supporting millions of smallholder farmers and workers in the cereal sector. However, Egypt faces challenges in cereal production due to limited arable land, water scarcity, climate change impacts, and soil degradation, with salt affected areas accounting for 25-30% of older agricultural lands. Additionally, reliance on traditional practices, insufficient agricultural extension services, and the high cost of modern technologies hinder productivity. Despite domestic efforts, Egypt remains heavily dependent on cereal imports, especially wheat and yellow corn, making the economy vulnerable to global price shocks and emphasizing the need for policies that enhance local production, food security, and economic development.